The Vegetable Zingo Vucavo Pesticidation Marketing Strategy - Nadila Savira; Eqy Astanza; Dian Fiola Sari (JASc (Journal of Agribusiness Sciences), 2019)
Soybean plants are the most related food crops, and the demand for soybean production is getting higher, but there are obstacles that occur so that the productivity of soybean plantsdecreases over time. In this activity we use experimental methods. This research was conducted at the Muhammadiyah University of North Sumatra and this activity was in accordance with a schedule that would take 4 months. By producing a product "ZINGO VUCAVA" which helps soybean farmers in eradicating the borer caterpillar pest so that the productivity produced in the future will increase. The product "VUCAVA ZINGO" is a pesticide made from natural ingredients, so it does not have a negative impact on the surrounding environment and health for consumers.